Immunological profiles, disease severity and clinical outcomes of HIV-infected and -uninfected patients admitted with COVID-19 in Tshwane - Rossouw, Theresa M. (University of Pretoria, 2025)
Thesis (PhD (Medical Immunology))--University of Pretoria, 2024.